An investigation into the use of intuitive control interfaces and distributed processing for enhanced three dimensional sound localization - Hedges, Mitchell Lawrence (Rhodes University, Faculty of Science, Department of Computer Science, 2016)
This thesis investigates the feasibility of using gestures as a means of control for localizing three dimensional (3D) sound sources in a distributed immersive audio system. A prototype system was implemented and tested which uses state of the art technology to achieve the stated goals. A Windows Kinect is used for gesture recognition which translates human gestures into control messages by the prototype system, which in turn performs actions based on the recognized gestures. The term distributed in the context of this system refers to the audio processing capacity. The prototype system partitions and allocates the processing load between a number of endpoints. The reallocated processing load consists of the mixing of audio samples according to a specification. The endpoints used in this research are XMOS AVB endpoints. The firmware on these endpoints were modified to include the audio mixing capability which was controlled by a state of the art audio distribution networking standard, Ethernet AVB. The hardware used for the implementation of the prototype system is relatively cost efficient in comparison to professional audio hardware, and is also commercially available for end users. the successful implementation and results from user testing of the prototype system demonstrates how it is a feasible option for recording the localization of a sound source. The ability to partition the processing provides a modular approach to building immersive sound systems. This removes the constraint of a centralized mixing console with a predetermined speaker configuration.
Keywords: Human-computer interaction; Acoustic localization; Sound -- Equipment and supplies; Acoustical engineering; Surround-sound systems; Wireless sensor nodes